Performance of hybrid maize genotypes under different moisture and nutrient regimes for improving productivity and nutrient use efficiency - Sharma, Savita; Mishra, D.P.; Kumar, Bhupender; Jewlia, H.R.; Singh, A.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted at New Delhi during kharif season of 2015 and 2016 to study theperformance of maize genotypes under different moisture and nutrient regimes. The results revealedthat the yields were significantly improved under normal condition as compared to stress at grainfilling stage in 2015 (low rainfall year), while in 2016 result was non-significant. Application offertilizer through Site Specific Nutrient Manamgenet (170:40:48 kg N:P2O5:K2O) resulted in significantincrease in maize yields in both the study years over absolute control. Among genotypes, PMH-4produced significantly higher grain, stover and biological yields during both the years. Nitrogenand Potassium content in grain, partial factor productivity and agronomic efficiency weresignificantly affected by applying stress at grain filling stage and SSNM based nutrient application.Amongst genotypes, significant variation in grain N and P was observed in 2015 but partial factorproductivity and agronomic efficiency was obtained higher with PMH-4, while lowest was withBio-9637 and Bio-9681. Therefore, it is concluded that the moisture and nutrient regimes imposessignificant effect on yield and nutrient use efficiency of maize hybrids.